Integrated solid waste management : a life cycle inventory. - McDougall, Forbes R., ....-; Franke, Marina, ....-; White, Peter R., ....- (Oxford : Blackwell, 2003)
Samenvatting:Combines the concepts of integrated waste management and of lifetimeassessment to provide a decision-making tool for waste managers andpolicy makers. Constructs a model to predict the overall environmentalimpacts and economic cost of municipal waste management systems, whichcan also be used to investigate the potential of new schemes ormodifications of the existing project. A computer model with completeinstructions is included on a 3.5" disk to be used with Excel 4.0, Lotus1-2-3 v.2.01 or later editions of either. Well indexed.
CDrom included
Keywords: Afvalstoffenmanagement; Levenscyclusanalyse (LCA).; Praktijkstudies